The impact of knowledge worker mobility through an acquisition on breakthrough knowledge - PARK, Haemin (Institutional Knowledge at Singapore Management University, 2018)
Acquisitions enable firms to access new knowledge from target firms, along with the scientists who created the knowledge, to enhance their own knowledge creation outcomes. We explore how the retention of target firm scientists and acquired knowledge characteristics affect new knowledge creation outcomes for the acquiring firms. Using a sample of 111,227 patents following 301 high-tech acquisitions in 1990–2000, we find that acquiring firms that avoid the exodus of target firm scientists increase their likelihood of creating highly impactful knowledge. Moreover, the characteristics of acquired knowledge and organizational context of the acquiring firms moderate this relationship. The positive effect of target firm scientist retention on the likelihood of creating highly impactful knowledge during the post-acquisition period is stronger when the acquired knowledge is complex, whereas such a relationship is weaker when the acquired knowledge stock is similar to that of the acquiring firm.